Simultaneous quantification of multiple bacterial metabolites using surface-enhanced Raman scattering. Issue 5 (10th January 2019) - Morelli, Lidia; Centorbi, Francesca Alessandra; Ilchenko, Oleksii; Jendresen, Christian Bille; Demarchi, Danilo; Nielsen, Alex Toftgaard; Zór, Kinga; Boisen, Anja
Abstract : We combine liquid–liquid extraction, SERS detection and partial least squares analysis for simultaneous quantification of bacterial metabolites in E. coli supernatant. Abstract : Given the commercial importance of the compounds produced by genetically modified organisms, there is a need for screening methods which facilitate the evaluation of newly developed strains, especially during the phase of proof-of-concept development. We report a time-efficient analysis method for the screening of bacterial strains, which enables the detection of two structurally similar secondary bacterial metabolites. By combining liquid–liquid extraction and surface-enhanced Raman scattering we were able to quantify p -coumaric acid and cinnamic acid, produced by genetically modified E. coli from tyrosine and phenylalanine, respectively. With the simple sample pre-treatment method, and by applying a partial least squares data analysis method, we simultaneously detected the analytes from four E. coli strains cultured in the presence or absence of tyrosine and phenylalanine.